Characterization of the complete chloroplast genome of Chinese privet Ligustrum lucidum (Oleaceae) - Wang, Rui-Hong (Mitochondrial DNA B Resour, 2018)
Ligustrum lucidum is a species of privet native to the southern half of China. It is often used as an ornamental tree, sometimes as a cultivar. In present study, we reported the Ligustrum lucidum chloroplast (cp) genome. The total chloroplast genome size of L. lucidum was 154,793 bp. In total, 124 genes were identified, including 81 protein-coding genes, 8 rRNA genes, and 35 tRNA genes. Twenty genes contained introns (clpP and ycf3 contained two introns) and 17 genes had two copies. The overall GC content of this genome was 38.2%. A further phylogenomic analysis of Oleaceae, including 21 taxa, was conducted for the placement of genus Ligustrum. The complete plastome of L. lucidum will provide a valuable resource for further genetic conservation, phylogenomic, and evolution studies of the genus and the family.